Pengetahuan dan sikap dokter gigi di jakarta barat terhadap penggunaan gtsl nilon termoplastik - Andy Wirahadikusumah; Clarice (Jurnal Kedokteran Gigi Terpadu, 2023)
Background: Removable partial dentures (RPDs) can be made out of a few different materials, one of them being thermoplastic nylon. Thermoplastic nylon RPDs have properties that make them superior to conventional dentures, such as their flexibility and resistance to fracture.To ensure the success of thermoplastic nylon RPDs, the dentists’ knowledge, skills, and accurate selection of cases is needed. Objectives: To obtain an overview of the knowledge and attitudes of dentists in Jakarta Barat regarding the use of thermoplastic nylon RPDs. Materials and methods: 113 dentists participated in this study. A validated questionnaire containing 20 items was given out via Google forms to measure the knowledge and attitudes of the dentists. Results: Different specializations were found amongst the respondents, with 85,8% (97) being general practitioners, 3,5% (4) prosthodontists, and 10,6% (12) other specialists. Most of the respondents have been working as a dentist for over 20 years (59,3%). However, the study found that majority of the respondents have poor knowledge (59,3%), followed by 21,2% (24) with adequate knowledge, and 19,5% (22) with good knowledge. The same can be said for attitudes, with 54,9% (62) having poor attitude, 28,3% (32) having adequate attitude, and only 16,8% (19) having good attitude. Conclusion: Based on the study results, it can be concluded that the knowledge and attitudes of dentists regarding the use of thermoplastic nylon is poor.